Construction of ferritin hydrogels utilizing subunit–subunit interactions - Masaru Yamanaka (Public Library of Science (PLoS), 2021)
Various proteins form nanostructures exhibiting unique functions, making them attractive as next-generation materials. Ferritin is a hollow spherical protein that incorporates iron ions. Here, we found that hydrogels are simply formed from concentrated apoferritin solutions by acid denaturation and subsequent neutralization. The water content of the hydrogel was approximately 80%. The apoferritin hydrogel did not decompose in the presence of 1 M HCl, 2-mercaptoethanol, or methanol but was dissolved in the presence of 1 M NaOH, by heating at 80°C, or by treatment with trypsin or 6 M guanidine hydrochloride. The Young’s modulus of the hydrogel was 20.4 ± 12.1 kPa according to local indentation experimentes using atomic force microscopy, indicating that the hydrogel was relatively stiff. Transition electron microscopy measurements revealed that a fibrous network was constructed in the hydrogel. The color of the hydrogel became yellow-brown upon incubation in the presence of Fe3+ ions, indicating that the hydrogel adsorbed the Fe3+ ions. The yellow-brown color of the Fe3+-adsorbed hydrogel did not change upon incubation in pure water, whereas it became pale by incubating it in the presence of 100 mM ethylenediaminetetraacetic acid (EDTA). The apoferritin hydrogel also adsorbed Co2+ and Cu2+ ions and released them in the presence of EDTA, while it adsorbed less Ni2+ ions; more Fe3+ ions adsorbed to the apoferritin hydrogel than other metal ions, indicating that the hydrogel keeps the iron storage characteristic of ferritin. These results demonstrate a new property of ferritin: the ability to form a hydrogel that can adsorb/desorb metal ions, which may be useful in designing future biomaterials.